HX008: a humanized PD-1 blocking antibody with potent antitumor activity and superior pharmacologic properties - Jibin Zhang; Ying Huang; Gan Xi; Faming Zhang (Taylor & Francis Group, 2020)
Through reactivating tumor-infiltrating lymphocytes, therapeutics targeting programmed cell death protein 1 (PD-1) demonstrate impressive clinical efficacy in the treatment of multiple cancers. In this report, we characterize HX008, a humanized IgG4S228P anti-PD-1 monoclonal antibody with an engineered Fc domain, in a series of in vitro assays and in vivo studies. In vitro, HX008 binds to human PD-1 with high affinity and potently suppresses the interaction of PD-1 with PD-L1 and PD-L2. The lack of detectable binding to complement C1q and Fc gamma receptor III-a (FcγRIIIa) suggested that HX008 maintained reduced antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity. A comparable enhancement of cytokine production and NFAT-driven luciferase expression in cell-based assays confirmed that HX008 could promote T-cell function as effectively as Nivolumab. In vivo antitumor activity studies were carried out within two special tumor models: 1) the MiXeno model with an adoptive transfer of human peripheral blood mononuclear cells into HCC827 xenograft mice; and 2) HuGEMM with human PD-1 gene knock-in syngeneic MC38-bearing mice. In both models, HX008 significantly inhibits tumor growth and shows an effective antitumor response comparable to approved anti-PD-1 drugs. Furthermore, in a pharmacokinetics study performed in cynomolgus monkeys, HX008 induced no immune-related adverse events when administered at 10 mg/kg. Although some anti-drug antibody effects were observed in the primate PK study, the safety and favorable pharmacokinetics demonstrated in human clinical trials validate HX008 as a suitable candidate for cancer immunotherapy. Taken together, our studies provide a fairly thorough characterization of HX008 and strong support for its further clinical research and application.